The Rule of Competence, Knowledge and Culture on the Leadership Role of Islamic Education Management - Arlen Mardayanti; Kasful Anwar; Afif Fuadi (Dinasti International Journal of Management Science, 2023)
The Literature Review article on the Influence of Competence, Knowledge and Culture on the Leadership Role of Islamic Education Management is a scientific article that aims to build a research hypothesis on the influence between variables to be used in further research, within the scope of Systematic Thinking in Islamic Education. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Competence influences the Leadership Role of Islamic Education Management; 2) Knowledge influences the Leadership Role of Islamic Education Management; and 3) Culture influences the Leadership Role of Islamic Education Management. Apart from these 3 exogenous variables that affect the endogenous variable, the Role of Leadership in Islamic Education Management includes many other factors, including the variables Public Speaking, leadership style and policy.